Short- and Long-Term Effectiveness of Supplementation with Non-Animal Chondroitin Sulphate on Inflammation, Oxidative Stress and Functional Status in Obese Subjects with Moderate Knee Osteoarthritis before and after Physical Stress: A Randomized, Double-Blind, Placebo-Controlled Trial - Mariangela Rondanelli; Niccolò Miraglia; Pietro Putignano; Gabriella Peroni; Milena Anna Faliva; Maurizio Naso; Clara Gasparri; Vittoria Infantino; Mara Nichetti; Nicola Volpi; Federica Capitani; Veronica Mantovani; et al. (MDPI AG, 2020)
It has recently been demonstrated that chronic supplementation with nonanimal chondroitin sulfate (nonanimal CS) in overweight subjects with knee osteoarthritis (OA) improves the function, pain and inflammation, but there are no studies of its effectiveness in an acute setting. In 48 obese subjects with moderate knee OA, we investigated the effectiveness of nonanimal CS supplementation for eight weeks on the inflammation, functional status, oxidative stress, cartilage catabolism markers, metabolic profile and body composition, by Dual-Energy X-ray Absorptiometry (DXA) at the baseline, after 15 days and at the end of the eight-week study. To evaluate the acute effectiveness on inflammation, 15-min cycle training sessions were done 15 days after the start of the study and at the end. C-reactive protein (CRP) was assayed in blood samples collected before and after the two cycling exercises. The 48 obese subjects (M and F, 20-50 years, body mass index (BMI) 30-35 kg/m2) were randomly assigned to an experimental group (N = 24, 600-mg tablet of nonanimal CS/day) or the control group (N = 24, placebo). The between-groups analysis of covariance showed a significant effect on the Western Ontario and McMaster Universities Arthritis index (WOMAC) scale (p = 0.000) and CRP (p = 0.022). For intra-group differences, the result was significant in the CS group for BMI, WOMAC, CRP, total cholesterol and Homeostasis Model Assessment (HOMA). In these obese adults with OA, nonanimal CS improved the inflammation, knee function, metabolic profile and body composition.